Rancang Bangun E-Library Berbasis Web pada SMP Negeri 2 Wewewa Tengah - Benediktus Aldolian Putra; Andreas Ariyanto Rangga; Dian Fransiska Ledi (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
At every educational institution there is a library for students to use at that institution. Likewise with SMP Negeri 2 Wewewa Tengah. At the school there is a library but it still uses a bookkeeping management system or is still written manually, while the number of active borrowers is almost all students carrying out the borrowing process at the school. The process of borrowing books in the library begins when students come to the library and tell the library staff that they want to borrow books. Then students select the books they want to borrow on the shelves provided. Next, the library staff records the borrower's data, such as full name, student identification number, and class, as well as data on books borrowed, such as book title, author, and inventory number in the ledger used as a borrowing register.). The school library has a strategic role and function in developing the potential of students from the entire academic community in the school environment. The library is part of the learning resources that every school has, a library that is still manual is something that needs to be created a system that can help with administrative activities. With the e-library, users can access it together with other users without having to wait in line. The search process is easier and faster because it is assisted by an information search engine that uses a database. This system presents a variant of the digital library, including a user page section that presents books available at the Central Wewewa State library